Measuring Leagile Supply Chain, Information Sharing, and Supply Chain Performance: Pre-Test and Pilot Test - Abdulameer, Susan Sabah; Yaacob, Noorulsadiqin Azbiya; Ibrahim, Yousif Munadhil (IJTech, 2020)
The aim of the current paper is to provide a valid and reliable instrument to ensure accurate results. Studies published on the supply chain and leagile supply chain (LASC) and information sharing (IS) as well as their impacts on supply chain performance (SCP) were reviewed, the measurements of the dimensions were adapted and developed, and the validity and reliability for the measures of the LASC, IS, and SCP dimensions were assessed. This assessment was done in two tests: the pre-test to establish the validity of the measures by experts and the pilot test to check the reliability of the measurements using SPSS.V.25. In the pre-test, the comments made by seven academician experts and four practitioners were used to rephrase items and to modify them according to the requirements of the manufacturing industries and in accordance with the Iraq context. Moreover, in the pilot test, some important factors were identified: on average, respondents took about 15 to 20 minutes to complete the questionnaire, and all the items were reliable and were sufficiently correlated with their constructs. The paper focuses on providing valid and reliable measurements for LASC, IS, and SCP as well as the developed measurements used for the decoupling point and testing them